(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The interdependence of greening agriculture and sustainable development of society have been discussed in the article. The ideology of greening agriculture, and sustainable development based on the requirements of the solution of contemporary problems facing society, namely to maintain the standards of rational use of natural resources and to ensure a favorable future for population. For this purpose, a number of measures and technologies are suggested.